Comparison of General Attitudes and Beliefs of Generations X, Y, and Z - Tahsin Akçakanat; Hasan Hüseyin Uzunbacak; Onur Sarıkaya (İmgelem)
Beliefs and attitudes significantly impact individuals' personal and professional lives. Differences in attitudes and beliefs can be observed among individuals. Moreover, from birth, individuals become part of a generation group of people born around the same years. Various characteristics differ among generations. The literature also suggests that there may be differences in attitudes and beliefs among generations. In this context, this research aims to shed light on the general attitudes and beliefs of Generation X, Y, and Z individuals. The study participants were academics and students from state universities in the Tr61 region of Turkey. The study included 228 participants from Generation X, 360 from Generation Y, and 477 from Generation Z. Data were collected from the participants through an online questionnaire. The analysis results indicate significant differences among Generation X, Y, and Z in terms of demand for fairness, need for achievement, need for comfort, and other downing. As one of the few empirical studies examining Generation Z and comparing Generation X, Y, and Z, this research has an original contribution.